Analysis of the #KaburAjaDulu Phenomenon in the Context of Migration of Indonesian Banyuwangi Workers Abroad: Analisis Fenomena #KaburAjaDulu dalam Konteks Migrasi Tenaga Kerja Indonesia (TKI) Banyuwangi ke Luar Negeri - Adam Jamal; Revienda Anita Fitrie (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The hashtag #KaburAjaDulu emerged as a social phenomenon that received significant public attention in response to economic and social conditions at the local and national levels, particularly related to limited job opportunities. This study aims to analyze this recently viral phenomenon in relation to the trend of Indonesian migrant workers (TKI), especially TKI from Banyuwangi, going abroad. The analysis was conducted using a quantitative approach, to examine official statistical data regarding the number and distribution of TKI before and after the hashtag #KaburAjaDulu. Secondary data was obtained from the Banyuwangi Regency Manpower, Transmigration, and Industry Office. The results of the analysis are expected to provide a comprehensive picture of the relationship between the #KaburAjaDulu phenomenon and the dynamics of labor migration from Banyuwangi. This study aims to provide policy recommendations for the government in managing labor migration effectively. Thus, it is expected to contribute to understanding the administrative and social aspects behind the mobility of TKI from Banyuwangi in the context of regional development and public administration.